Transformation Index BTI 2014: political management in international comparison (Verlag Bertelsmann Stiftung, 2014)
Managing the peaceful transition of authoritarian states to democracy and a market-economic system represents a tremendous challenge. Whether it comes to reconstituting the coherency of the state following armed conflict, expanding participation rights and the rule of law in emerging democracies, overcoming corrupt structures, fighting poverty and inequality, or establishing clear rules for stable market-economic competition, the requirements are enormous, and the pressure on responsible leaders is intense. After all, the quality of political management makes an essential contribution to the s
Description based upon print version of record
Keywords: Electronic books